2016
DOI: 10.1136/bmjspcare-2016-001204.2
|View full text |Cite
|
Sign up to set email alerts
|

How current UK research addresses out of hours palliative care

Abstract: IntroductionIn 2015 the Palliative and end of life care Priority Setting Partnership (PeolcPSP), facilitated by the James Lind Alliance, published a top-ten list of unanswered questions relating to palliative and end-of-life care research. These were ranked in accordance with responses from people in the last years of life, current/bereaved carers and professionals working with people at the end-of-life.The highest ranked question was: “What are the best ways of providing palliative care outside of working hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the current review, very few papers on out-of-hours care were identified, despite this being identified as the number one priority for research according to the JLA [ 98 ]. Given the current dearth of evidence on out-of-hours and continuity of care as well as the national focus on improving out of hours care [ 101 ], this will remain an important direction for research in the future. The crucial link between eHealth integration improvements and the quality of out-of-hours palliative care provision is also an important potential area for research.…”
Section: Discussionmentioning
confidence: 99%
“…In the current review, very few papers on out-of-hours care were identified, despite this being identified as the number one priority for research according to the JLA [ 98 ]. Given the current dearth of evidence on out-of-hours and continuity of care as well as the national focus on improving out of hours care [ 101 ], this will remain an important direction for research in the future. The crucial link between eHealth integration improvements and the quality of out-of-hours palliative care provision is also an important potential area for research.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great need for access to good out of hours palliative care [22] services, but this was recognised more by the MOOC participants than by the members of the consensus group. Once again, this may reflect the daily experience of staff.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, it currently receives less than 1% of all cancer research spending, despite one-third of hospital inpatients being in the last year of life. 16 Both palliative care provision and research are dependent on charitable giving and consequently, activity fluctuates significantly with the economic climate. For example, the COVID-19 pandemic resulted in suspension of many charity-funded research grants.…”
Section: Introductionmentioning
confidence: 99%